2016
DOI: 10.1094/pdis-04-15-0384-re
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Pathogenicity of Ralstonia solanacearum Causing Tobacco Bacterial Wilt in China

Abstract: Bacterial wilt caused by Ralstonia solanacearum is the most serious soilborne disease of tobacco (Nicotiana tabacum) in China. In this study, 89 strains were collected in 2012 to 2014 from across the four major tobacco-growing areas in China. The strains were identified as phylotype I by multiplex polymerase chain reaction and further divided into seven sequevars based on polymorphisms in the endoglucanase (egl) gene. Among the seven sequevars, four (15, 17, 34, and 44) have been previously described as pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
3
38
0
1
Order By: Relevance
“…contained sequevar 17, 44, 54 and 55. It was surprising that the sequevar 54 (reported on tobacco R. solanacearum strains recently) (Li et al 2016) and the new sequevar 55 were only found in areas with moderate to high elevations. The new sequevar may gather R.solanacearum strains evolving to adapt to the high elevations environment.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…contained sequevar 17, 44, 54 and 55. It was surprising that the sequevar 54 (reported on tobacco R. solanacearum strains recently) (Li et al 2016) and the new sequevar 55 were only found in areas with moderate to high elevations. The new sequevar may gather R.solanacearum strains evolving to adapt to the high elevations environment.…”
Section: Discussionmentioning
confidence: 92%
“…1). Among the eight sequevars, sequevar 13,14,15,17,34,44, and 54 had been reported in Chinese tobacco R. solanacearum strains by Li et al (2016), and sequevar 55, the new one, has not been previously described. The new sequevar may be an evidence that verified the ongoing evolutionary of phylotype I.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Los filotipos se subdividen en secuevares, los cuales están basados en la secuencia nucleotídica del gen Egl, que codifica para una endoglucanasa (Fegan y Prior, 2005). Hasta el momento, se han identificado 54 secuevares en el complejo de R. solanacearum (Li et al, 2016); los secuevares causantes de la enfermedad Moko en plátano son el 3, 4, 6, 24, 25, 41 y 53. En el continente americano la enfermedad Moko está presente desde Brasil hasta Estado Unidos (Sanchez-Perez et al, 2008;Norman et al, 2009;Hong et al, 2012;Albuquerque et al, 2014).…”
Section: Ralstonia Solanacearum Strainsunclassified